Performance Analysis of Supercapacitor Integrated PV Fed Multistage Converter with SMC Controlled VSI for Different Load Conditions - Shruti Pandey; Bharti Dwivedi; Anurag Tripathi (Institute of Advanced Engineering and Science, 2018)
The proposed work comprises of an MPPT controlled Photovoltaic (PV) source, in conjunction with a supercapacitor, cascaded with a Sliding Mode Controlled (SMC) Inverter, supplying variable linear and nonlinear loads. The effects of varying solar irradiation and its intermittency have been effectively managed by the MPPT controlled boost converter and charge controlled supercapacitor respectively. The charge controller bucks and boosts the terminal voltage and realizes the power flow in a bidirectional manner. Seamless action has been obtained by the proposed model under varying irradiation and for varying load conditions. The performance of the SMC controlled Inverter, when compared with a PI controlled Inverter, has been found to be superior in terms of power quality and robustness of the supply system